Complications associated with gestational toxoplasmosis - congenital: An integrative review (Research, Society and Development, 2024)
Objective: To review the complications associated with congenital gestational toxoplasmosis. Methodology: A qualitative descriptive study, based on a bibliographic review from the Virtual Health Library (VHL). Articles published between 2018 and 2022, written in Portuguese, and addressing the proposed theme were considered. Results and Discussion: The search resulted in 4 studies that discuss complications of gestational toxoplasmosis, such as congenital anomalies and visual deficits. Most cases highlight the importance of early diagnosis and interventions to prevent severe complications. Conclusion: Gestational toxoplasmosis poses a significant challenge to public health due to its severe implications for maternal and neonatal health. Robust screening and monitoring strategies, along with education on preventive practices, are essential to mitigate the risks associated with the disease.